1998
DOI: 10.1097/00007632-199811150-00013
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Endoscopic Approach to the Thoracolumbar Spine

Abstract: The anterior endoscopic approach to the lumbar spine involves minor trauma, results in rapid recovery and less pain, and produces good results aesthetically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 10 publications
1
14
0
1
Order By: Relevance
“…Dr Newton [16] kindly forwarded to us his latest paper accepted for publication in Spine. We were therefore left with ten papers 1 [5,6,8,12,14,[16][17][18][19][20] dealing either exclusively or partially with thoracoscopic anterior release in spinal deformities and their complications. We carefully reviewed each paper in its entirety to answer our questions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dr Newton [16] kindly forwarded to us his latest paper accepted for publication in Spine. We were therefore left with ten papers 1 [5,6,8,12,14,[16][17][18][19][20] dealing either exclusively or partially with thoracoscopic anterior release in spinal deformities and their complications. We carefully reviewed each paper in its entirety to answer our questions.…”
Section: Methodsmentioning
confidence: 99%
“…As to the surgical endoscopic technique used to approach thoracolumbar curves as described by Burgos et al [1], we took that to be beyond the scope of this review, which deals specifically with thoracic deformities.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Instead of using the porcine model strictly for teaching purposes, some authors have described the use of a porcine model to test the feasibility of complex endoscopic approaches [2,19]. Rubino et al [19] used a 30°angle endoscope to view the upper thoracic and cervical spine with an entrance portal at the anterior border of the sternocleidomastoid muscle.…”
Section: Additional Uses Of a Porcine Modelmentioning
confidence: 99%
“…These authors reported excellent visualization of the entire cervical spine. Burgos et al [2] used swine to test the feasibility of a method for exposing the thoracolumbar spine. Before attempting the procedure in patients, these authors determined that in swine, the most effective method for exposure was an initial standard thoracoscopic approach followed by a retroperitoneal endoscopic approach.…”
Section: Additional Uses Of a Porcine Modelmentioning
confidence: 99%
See 1 more Smart Citation